2018
DOI: 10.3389/feart.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rain Gauge Quality Control and Interpolation on Streamflow Simulation: An Application to the Warwick Catchment, Australia

Abstract: Rain gauges are widely used to obtain temporally continuous point rainfall records, which are then interpolated into spatially continuous data to force hydrological models. However, rainfall measurements and interpolation procedure are subject to various uncertainties, which can be reduced by applying quality control and selecting appropriate spatial interpolation approaches. Consequently, the integrated impact of rainfall quality control and interpolation on streamflow simulation has attracted increased atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This poses a major issue when analyzing past heavy rainfall events. Gridded data sets derived from gauge data are also subject to spatial errors originating from the interpolation techniques used (Liu et al., 2018; Tozer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This poses a major issue when analyzing past heavy rainfall events. Gridded data sets derived from gauge data are also subject to spatial errors originating from the interpolation techniques used (Liu et al., 2018; Tozer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While notable work has been done with radar rainfall estimation for flood events (Cusworth, 1997; Hoy, 1975; Liu et al., 2018; Sun et al., 2000) and investigating drop size distributions (Bringi et al., 2009; Thurai et al., 2010) in Australia, there have not yet been any long‐term radar studies that focus on rainfall event characteristics on a national scale, despite such studies existing in other parts of the world. Furthermore, initial identification of extreme rainfall events in many studies both in Australia and overseas is performed using a rain gauge network, before radar data is later used to investigate event attributes in more detail (Hitchcock et al., 2021; Lee & Kim, 2007; Moral et al., 2020; Rigo & Llasat, 2004; Schumacher & Johnson, 2006; L. Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the usage of rain gauge data, data pre-processing (i.e., gridding) is required to change its spatial distribution from isolated points to a distributed grid. Many previous studies have attempted to determine the optimal interpolation method to use with point rain gauges [5][6][7]; unfortunately, the rain gauges can be affected by atmospheric effects [8] and the possibility of instrument failure, among other issues. When applying interpolation methods, the number and location of rain gauges in some basins are often insufficient and, in some instances, may be extremely poor.…”
Section: Introductionmentioning
confidence: 99%
“…Ly et al (2013) found no optimal spatial interpolation method for operational hydrology, and that interpolation performance often depended on the density of the gauge network, the spatial and temporal resolution of the data, and parameters such as those used by the semi-variogram in kriging. Mair and Fares (2011); Chen et al (2017), and Liu et al (2018) compared interpolation methods based on their ability to simulate streamflow, with each study using a different hydrological model and catchment.…”
mentioning
confidence: 99%